MEMBANGKITKAN POTENSI DIRI DAN MINAT SISWA DALAM BELAJAR BAHASA ARAB DENGAN NILAI-NILAI HYPNOTEACHING - Akhsan Akhsan; Ahmadi Muhammadiyah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
The most important obstacle today in learning Arabic is that the awareness of the importance of Arabic in students has not been fully formed. This fact occurs because Arabic learners and teachers, especially in Indonesia, are still trapped in policies (regulations regarding the continuity of learning in class, time and space issues), curriculum (objectives and boundaries of competence), and methodology (theories that must be put into practice). Coupled with the "image" and "mindset" that has been formed in society that Arabic is only the language of religion. Make students aware that Arabic is one of the international languages ​​and it is useful in their world life. This problem is a fundamental problem which academics and Arabic language practitioners have to slowly resolve. The purpose of learning Arabic must be shifted from "teaching the language" to "teaching the language", teaching methodology must be "constructed" from practicing theory and curriculum to exploring potential and arousing student interest. With the application of Hipnoteaching values, it is hoped that teachers will be able to design Arabic language learning that is able to increase the potential, talents, and interests of students in Arabic. Hypnoteaching values ​​according to the results of this study, it can be adopted in Arabic learning with the following concepts : 1) Place, Location and Arabic Study Room Setting, 2) Mental and psychological settings of Arabic teachers and students, 3) Early Learning Stimulus, 4) Setting communication styles in Arabic learning, 5) Enabling the class with practice is not just a transfer of knowledge or knowledge of Arabic, 6) Evaluation and 7) Closing Activities of Learning Arabic.